The ‘good chap’ and a ‘new type of judge’: the UK constitution under stress - Turenne, Sophie (Teoría y Realidad Constitucional, 2022)
This paper argues that the broader legal and extra-legal environment matter to understand the set of beliefs and attitudes which condition judicial activity and therefore influence the design of judicial appointments. Attitudes to the separation of powers are discussed and illustrated by the consideration of, in turn: the history of appointments to the higher courts, the recent accompanying changes to the role of the Lord Chancellor, the changing perception of the judiciary in the media and political circles, the present constitutional role played by the Supreme Court and the vulnerability of judges to politically motivated attacks. In the UK, the consideration of such factors points towards rejection of greater involvement of the Lord Chancellor in the UK Supreme Court appointments, at least for now or until a sense of basic constitutional propriety prevails among all political institutions.